Identification of odor-active compounds in Nile tilapia (Oreochromis niloticus) from recirculated aquaculture systems: A case study with different depuration procedures - Rodrigues da Silva, Mariana; Loos, Helene; Büttner, Andrea (Food Research International, 2024)
Off-flavors are a major challenge for companies using recirculated aquaculture systems (RAS). In the presented work, we comprehensively characterize the odorant composition of Nile tilapia (Oreochromis niloticus) raised in RAS and compare the impact of two depuration processes on the odorant composition and aroma profile of the fish. Fish collected from the production tank and after two different tank pre-disinfection approaches in the depuration process (high pH versus H2O2) were investigated. A combined sensory-instrumental investigation revealed the presence of 115 odorants, of which 83 were successfully identified. The compounds decanal, tridecanal, (Z)-1,5-octadien-3-one, octane-2,3-dione, benzophenone, non-3-yn-1-ol, γ-dodecalactone, (Z)-geranylacetone, 2,3-diethyl-5-methylpyrazine, 1-methylpyrrolidin-2-one, 2-acetyl-2-thiazoline, benzothiazole, skatole, and 5α-androst-16-en-3-one were detected with the highest flavor dilution factors and are described for the first time as odor-active compounds in fish from RAS. The results indicate that depuration decreased the levels of 78 different odorants from the fish, including the potent earthy smelling odorants geosmin, isoborneol and 2,3-diethyl-5-methylpyrazine.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Aroma extract dilution analysis; Gas chromatography-mass spectrometry; Gas chromatography–olfactometry; Smell; Solvent-assisted flavor evaporation; Two-dimensional gas chromatography with mass spectrometry and olfactometry